The Contribution of Interfaith Dialogue in Transforming Nuclear Conflict between the United States and the Islamic Republic of Iran - Andrea Rayi Galuh Palita; Elyzabeth Bonethe Nasution (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2021)
The nuclear conflict between the US and Iran is one that is complicated to be resolved. Although the prevailing conflict has not reached the point of war, the political and social tensions precipitate concerns to the international security. Various stakeholders are involved, not only the government, but also the society as external parties in influencing the conflict. Therefore, this research centralises on examining interfaith dialogue as one of the approaches in efforts to transform the conflict through describing and analysing its process, role, and limitations in addressing nuclear conflict between the US and Iran. Sample data are obtained through a literature study by collecting secondary data. This research draws on three examples of interfaith dialogue between the US and Iran upon examining the interfaith dialogue approach's process, role, and limitations examined through the Constructivist theory, which were conducted by (i) USCCB and the Society of the Seminary Teachers of Qom, (ii) MCC and IRCS with IKRI, and (iii) Washington National Cathedral with Former President Khatami. This research indicates that the roles of interfaith dialogue are to prevent the escalation of conflict escalation and to facilitate conflict transformation process. However, this approach still needs to overcome numerous limitations as conflicted parties still show no signs of subsiding. These limitations are rooted from the strong ideas and identities of the two countries and the process of the approach itself. Bahasa Indonesia Abstract: Konflik nuklir antara AS dan Iran memang rumit untuk diselesaikan. Meskipun konflik yang terjadi belum sampai pada titik perang, ketegangan politik dan sosial antara kedua negara memicu kekhawatiran terhadap keamanan internasional. Berbagai pemangku kepentingan terlibat dalam konflik ini, tidak hanya pemerintah, tetapi juga masyarakat sebagai pihak eksternal dalam memengaruhi konflik tersebut. Oleh karena itu, penelitian ini memusatkan pada kajian dialog antaragama sebagai salah satu pendekatan upaya transformasi konflik melalui pendeskripsian dan analisis proses, peran, dan keterbatasan dialog antaragama dalam menangani konflik nuklir antara AS dan Iran. Data sampel diperoleh melalui studi kepustakaan dengan mengumpulkan data sekunder. Penelitian ini mengacu pada tiga contoh dialog antara pihak AS dan Iran untuk mengkaji proses, peran, dan keterbatasan pendekatan dialog antaragama yang dikaji melalui Teori Konstruktivis. Ketiga dialog tersebut dilakukan oleh (i) USCCB dan Society of the Seminary Teachers of Qom, (ii) MCC dan IRCS dengan IKRI, dan (iii) Washington National Cathedral dengan Mantan Presiden Khatami. Hasil dari penelitian ini menunjukkan bahwa peran dialog antaragama dalam menangani isu nuklir AS dan Iran saat ini adalah untuk mencegah eskalasi konflik serta memfasilitasi proses transformasi konflik. Namun, seiring dengan belum meredanya konflik, pendekatan dialog ini masih memiliki banyak keterbatasan yang didasari oleh kuatnya identitas agama dari kedua negara serta karena proses dialog itu sendiri.